Membangun Karakter “Generasi Hebat” Melalui Sosialisasi Penguatan Literasi Di Pondok Pesantren Bequranic Bengkalis - Aisyah Nuramini; Nelly Hastuti (SIGMA : Jurnal Sinergi Mengabdi, 2025)
This community service program discusses efforts to build the character of a great generation in Islamic boarding schools through strengthening literacy. Low literacy rates in several Islamic boarding schools are a major concern, as they impact the less than optimal character formation of students and hinder the achievement of the Islamic boarding school's vision of producing a generation that is religious, intelligent, and capable of facing the challenges of the times. Therefore, this community service program focuses on improving students' reading, writing, digital, and critical literacy skills. The method used includes the PAR (Participatory Action Research) method by involving active participation and communication or research subjects in every stage, from problem identification to implementation and evaluation. The results of the community service show a significant increase in literacy skills and the formation of students' character who are more religious, have integrity, and are able to think critically. This program makes a real contribution to producing the next generation of the nation who are superior and have good morals, and is recommended as a model for literacy-based character development in other Islamic boarding schools.